(untitled) (Al-Aasar, 2025)
Various countries around the world have produced interpretations in different languages. Among them one is "Tafsir Madarik" authored by Allama Abu al-Barkat Abdullah bin Ahmad bin Mahmood al-Nasafi. Its complete title is "Madarik al-Tanzil wa Haqaiq al-Ta’wil". It has been translated into Urdu, and the translation style is excellent and linguistically rich. It meticulously refutes the false beliefs of misguided sects and is entirely free from Israeli narrations. It provides detailed explanations of each verse, including the opinions of various scholars. Surah Al-Fath is a Medinan Surah, consisting of 29 verses and four sections, located in the 26th Juz. The first verse of this blessed Surah heralds the bright victory of the Prophet (peace be upon him), hence its name "Surah Al-Fath". It narrates many significant events such as the Prophet’s true dream, the Pledge of Ridwan, the Treaty of Hudaybiyyah, the Conquest of Khaybar, the Expedition of Umrat al-Qada, and the Conquest of Mecca. Since "Tafsir Madarik" is an outstanding interpretation, it also presents jurisprudential issues from the Hanafi perspective. Therefore, in this article, an analytical study of the events in Surah Al-Fath has been presented in light of "Tafsir Madarik".